An ecdysterone-responsive puff site in Drosophila contains a cluster of seven differentially regulated genes. - Restifo, L.L.; Guild, G.M. (Journal of Molecular Biology, 1986)
We have determined the molecular organization of an ecdysterone-responsive puff site in Drosophila melanogaster. The 71E puff site contains a tightly linked cluster of at least seven genes within a neighborhood of 10 X 10(3) base-pairs. All the genes are expressed in a tissue-specific manner in either the larval or the prepupal salivary gland. However, these genes can be divided into two groups on the basis of their temporal pattern of transcription. Six of the genes are expressed only in prepupal salivary glands and are arranged as three divergently transcribed pairs. Nestled within this region is one gene expressed primarily in late third-instar salivary glands. We conclude that this developmentally complex puff site contains six members of the ecdysterone-induced "late"-gene set and one member of the ecdysterone-regulated "intermolt" -gene set. Additional complexity is found at the transcript level: a heterogeneously sized population of RNA molecules arises from each of the seven genes.